Re-imagining the Ambivalent: The Political Trajectory of Lungi from Pre-Colonial East Bangla to Post-Independent Bangladesh - Mahbub, Rifat (Spectrum, 2023)
Lungi, Bangladeshi men’s most common informal clothing, occupies an ambivalent position in the country’s sartorial culture because of its inherent status of being anti-modern and anti-formal. Bangladeshi postcolonial poet Kaiser Haq’s (2007) ground-breaking poem, “Ode on the Lungi '' and the growing body of academic papers focusing on the poem have already constructed lungi as a discursive symbol to challenge and decentralise the colonial construction of cultural hierarchies that underpinned such a postcolonial legacy of sartorial discrimination. Important as they are, these studies do not engage with lungi’s actual historical trajectories of resistance and struggle where men in lungi participated as active agents to challenge authoritative power regimes. By investigating the key episodes of “politics of the people'' (Guha, 1988, p. 40) from pre-colonial east Bangla to present-day Bangladesh, the paper reclaims lungi’s active yet metaphorical performative at each stage of collective struggles that ultimately led to the 1971 War of Independence (Muktijuddho), where lungi was the main attire of the male freedom fighters (Muktijoddhas). This paper argues that the national/cultural ambivalence around lungi in Bangladesh is rooted in its simultaneous trope of being a clothing of people who are at the edges of political power, yet their collective resistance can be subversive. This is one of the reasons why a ban on lungi in contemporary Bangladesh, although more common than before, often becomes a topic of heated debates and discussions among the educated, middle-class communities. Spectrum, Volume 17, June 2022: 47-65